Multifunctional additive, solid electrolyte and preparation method and application thereof

By using fluoraniline and its derivatives as multifunctional additives in lithium-ion batteries, combined with substituents such as fluorine atoms, the low ion conductivity and electrochemical stability of polymer solid electrolytes are solved, and efficient lithium ion transmission is achieved And battery performance improvement.

CN119241370AActive Publication Date: 2025-01-03WUHAN UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411374760.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The polymer solid electrolyte has low ionic conductivity, and existing additives have shortcomings in electrochemical stability and lithium salt dissociation effects, which limits its application in lithium-ion batteries.

Method used

Fluoraniline and its derivatives are used as multifunctional additives to enhance the ionic conductivity of the electrolyte through the interaction between amino groups and lithium salts and bind to substituents such as fluorine atoms, chlorine atoms, alkoxy groups, phenyl and nitrile groups. Electrochemical stability to form efficient solid electrolytes.

Benefits of technology

The ionic conductivity reaches 10-4S/cm or above, and the electrochemical window reaches 5.2V, which significantly improves the cycle life and safety of solid-state batteries. It is suitable for a variety of lithium-ion solid-state electrolyte polymer systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241370A_ABST
    Figure CN119241370A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and provides a multifunctional additive, a solid electrolyte and a preparation method and application thereof, the additive comprises fluoroaniline and derivatives thereof, the structural general formula of the additive is # imgabs0 #, R1 comprises fluorine atoms, R2 is a single bond or alkyl, and x is an integer of 1-5. According to the invention, fluoroaniline and a homologue thereof are taken as the solid electrolyte additive, and the additive can generate relatively strong interaction with anion groups of various lithium salts due to the amino group, so that dissociation of the lithium salts is promoted, and the ionic conductivity of the solid electrolyte is improved to 10 <-4 > S / cm or above; meanwhile, the oxidation resistance of the solid electrolyte is also improved, and a practical research scheme is provided for developing a high-performance solid lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a multifunctional additive, a solid electrolyte, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have been widely used in energy storage, electric vehicles, laptops, mobile phones and other consumer electronics. However, the electrolytes used in commercial lithium-ion batteries are flammable, volatile and fluid, which hinder the reliability and safety of lithium-ion batteries. Solid electrolytes have intrinsic safety and show good application potential. Polymer solid electrolytes, as an important branch in the field of solid electrolytes, have become a hot topic in solid-state battery research due to their good flexibility and easy processing, high compatibility with current battery manufacturing processes, and effective adaptation to the interfaces of a variety of positive and negative electrode materials. However, the main challenge faced by polymer solid electrolytes in practical applications is their low ionic conductivity, which is caused by the low dissociation efficiency of lithium salts in the polymer matrix.

[0003] A variety of strategies have been developed to address the problem of low ionic conductivity. 12 Solid electrolytes such as lithium ions are used to promote the dissociation of lithium salts and construct efficient lithium ion transmission channels. Although this method can effectively improve the ionic conductivity, the high cost of inorganic additives and the difficulty in controlling uniformity during the preparation process limit its application in large-scale production. On the other hand, attempts to incorporate organic additives into polymers can bring certain performance improvements, such as succinonitrile (Energy Chem. 2022, 74: 18) and methyl propionate (Adv. Energy Mater. 2022, 12, 2102932). However, these additives often face the challenge of insufficient electrochemical stability and are prone to degradation during battery operation, affecting the long-term stability and functionality of the electrolyte. Therefore, a new type of functional additive is developed to have excellent electrochemical stability, be able to resist adverse factors in the environment, and exhibit efficient dissociation of lithium salts, thereby significantly improving the ionic conductivity and electrochemical window of polymer solid electrolytes.

[0004] CN 115020818 A discloses a polymer electrolyte additive of 2,3,4,5,6-pentafluorophenylboric acid. The ionic conductivity of the solid electrolyte introduced with the additive is 3.06×10 -5 Scm -1 , the voltage window is 5V, and the ionic conductivity performance of this electrolyte does not reach the average value of current electrolytes (10 -4 Scm -1). This shows that the additive has limited effect on improving the electrochemical performance of solid electrolytes. The possible reason is that the additive contains hydroxyl functional groups, which are electrochemically unstable and will react with lithium metal. In addition, the additive has no real effect on the dissociation of lithium salts, which leads to its limited effect on improving ionic conductivity. Therefore, a solid electrolyte with an ionic conductivity of 10 is needed. -4 Scm -1 Solid electrolyte additives of orders of magnitude. Summary of the invention

[0005] In view of this, the present invention proposes an ionic conductivity of 10 -4 Scm -1 A solid electrolyte additive with an electrochemical window of 5.2V, a solid electrolyte containing the additive, and a preparation method and application thereof.

[0006] The technical solution of the present invention is achieved as follows: In the first aspect, the present invention provides a multifunctional additive, the additive comprises fluoroaniline and its derivatives, and the general structural formula thereof is:

[0007]

[0008] Wherein, R1 includes a fluorine atom, R2 is a single bond or an alkyl group, and x is an integer of 1 to 5.

[0009] Specifically, the amino group (NH2) has strong polarity and nucleophilicity. Since the additive of the present invention contains an amino group, it can react with the anionic group of the lithium salt (such as PF6 - 、BF4 - This interaction helps the dissociation of lithium salts and generates more free lithium ions (Li + ), thereby improving the ionic conductivity of the solid electrolyte.

[0010] Fluorine atoms have high electronegativity and small atomic radius, which can enhance the stability of molecules. The introduction of fluorine atoms into the benzene ring can improve the antioxidant properties of the molecule and reduce the decomposition and degradation of the electrolyte under high voltage, thereby improving the cycle life and safety of solid-state batteries.

[0011] Because fluoroaniline and its derivative additives have both amino groups and fluorine atoms, they exhibit multifunctionality in solid-state electrolytes: improving ionic conductivity and enhancing stability, thereby improving the overall performance and safety of the battery.

[0012] On the basis of the above technical solution, preferably, the R1 further comprises one or more of a chlorine atom, an alkoxy group, a phenyl group, a nitrile group and an alkyl group.

[0013] Specifically, chlorine has a high electronegativity and can enhance the polarity of the molecule; this polarity helps to interact with the lithium salt anion, promote the dissociation of the lithium salt, and improve the ionic conductivity; the chlorine atom can also improve the chemical stability of the molecule and reduce the decomposition of the electrolyte under high voltage. Alkoxy groups (such as ethoxy) have a strong electron supply ability, which can stabilize the anions of the lithium salt and promote the migration of lithium ions; in addition, the introduction of alkoxy groups increases the flexibility of the molecule, helps to improve the mechanical properties and interface contact of the electrolyte, and improves the cycle life. Phenyl groups can stabilize the anions of the lithium salt through π-π interactions and improve the ionic conductivity; in addition, the introduction of phenyl groups also increases the rigidity of the molecule and improves the thermal stability and antioxidant properties of the electrolyte. The nitrile group has a strong polarity and coordination ability, and can form a stable complex with the lithium salt anion, promoting the dissociation and migration of lithium ions; the introduction of the nitrile group also improves the antioxidant properties of the molecule and extends the cycle life of the battery.

[0014] The present invention introduces chlorine atoms, alkoxy groups, phenyl groups or nitrile groups on the basis of fluorine atoms, which can regulate the physical and chemical properties of the electrolyte at the molecular level, thereby further improving the ionic conductivity, cycle life and antioxidant properties of the solid electrolyte. This diversified substituent design provides more possibilities and flexibility for the performance optimization of solid-state batteries.

[0015] On the basis of the above technical scheme, preferably, when x≥3, the additive is a solid powder at room temperature, which is easily soluble in common electrolyte solvents: fluoroethylene carbonate (FEC), 1,3-dioxolane (DOL), diethyl carbonate (DEC), etc. or commonly used solvents for preparing solid electrolytes by casting method: dimethylformamide (DMF), N-methylpyrrolidone (NMP), acetonitrile, etc.; when x≤2, the additive is a liquid at room temperature.

[0016] In a second aspect, the present invention provides a solid electrolyte comprising a lithium salt, a polymer matrix and the above-mentioned additives.

[0017] On the basis of the above technical solution, preferably, the amount of the additive is 0.5%-10% of the total mass of the lithium salt and the polymer matrix.

[0018] On the basis of the above technical scheme, preferably, the polymer matrix is ​​one or more combinations of polyether, polyvinylidene fluoride and its homologues or cyclic ether, acrylate and its homologues; the lithium salt is one or more combinations of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluorosulfonyl)imide.

[0019] In a third aspect, the present invention provides a method for preparing a solid electrolyte, comprising the following steps:

[0020] S1, in an argon protective atmosphere of a glove box, uniformly mixing the additive and the polymer matrix to obtain a mixed solution I;

[0021] S2, mixing the mixed solution I with a lithium salt to obtain a precursor solution, and heating the solution until the solvent evaporates to obtain a solid electrolyte.

[0022] On the basis of the above technical scheme, preferably, in step S1, when the polymer matrix is ​​polyether, polyvinylidene fluoride and its homologues, it is first dissolved in an organic solvent and then mixed with the additive; the mass ratio of polymer matrix: organic solvent is (5-20):100, and the organic solvent is dimethylformamide or acetonitrile.

[0023] Based on the above technical solution, preferably, in step S2, the concentration of the lithium salt is 1-3 mol / L.

[0024] On the basis of the above technical scheme, preferably, when the polymer matrix is ​​cyclic ether, acrylate and its homologues, in step S2, after the mixed solution I is mixed with the lithium salt, an initiator is added to obtain a precursor solution.

[0025] On the basis of the above technical solution, preferably, the initiator is one or more combinations of aluminum trifluoromethanesulfonate, stannous trifluoromethanesulfonate and azobisisobutyronitrile, and the amount of the initiator is 0.1%-0.5% of the total mass of the mixed solution I and the lithium salt.

[0026] In a fourth aspect, the present invention also provides the use of solid electrolytes in the preparation of lithium batteries.

[0027] The multifunctional additive, solid electrolyte and preparation method and application thereof of the present invention have the following beneficial effects compared with the prior art:

[0028] (1) The additive of the present invention includes fluoroaniline and its homologues. Due to the presence of amino groups and fluorine atoms, the multifunctional electrolyte additive can generate strong interactions with the anion groups of various lithium salts, promote the dissociation of lithium salts, and thus improve the ionic conductivity of the solid electrolyte (10 -4 S / cm or more). In addition, the introduction of fluorine atoms improves the antioxidant properties of the molecule and reduces the decomposition and degradation of the electrolyte at high voltage, thereby improving the cycle life and safety of solid-state batteries.

[0029] (2) The present invention further introduces halogen atoms, alkoxy groups, hydrogen atoms, phenyl groups, nitrile groups or alkyl groups on the basis of fluorine atoms, and regulates the physical and chemical properties of the electrolyte at the molecular level, thereby further improving the ionic conductivity, cycle life and antioxidant properties of the solid electrolyte, providing more possibilities and flexibility for the performance optimization of solid-state batteries.

[0030] (3) This multifunctional electrolyte additive has a wide range of application value and can be applied to a variety of lithium-ion solid electrolyte polymer systems, including polyethers, cyclic ethers, acrylates, polyvinylidene fluoride and other polymers and their derivatives, providing a practical research solution for the development of high-performance solid-state lithium-ion batteries.

[0031] (4) The fluoroaniline derivative additive provided by the present invention is easily soluble in a variety of common electrolyte solvents and solvents used to prepare solid electrolytes. The fluoroaniline derivative additive can be introduced into the solid electrolyte through a solution method that is simple and easy to implement, which is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 1 is the electrochemical impedance spectra of the polymer electrolytes prepared in Example 1 of the present invention and Comparative Example 1;

[0034] Figure 2 1 is a linear sweep voltammetry curve of the polymer electrolyte prepared in Example 1 of the present invention and Comparative Example 1;

[0035] Figure 3 The Li / / Li symmetric battery assembled with the polymer electrolyte prepared in Example 1 and Comparative Example 1 was -2 , 0.5mAh cm -2 The voltage-time curve diagram below;

[0036] Figure 4 is a scanning electron microscope photograph of the Li / / Li symmetric battery assembled with the polymer electrolyte prepared in Example 1 and Comparative Example 1 after 20 cycles;

[0037] Figure 5 It is a cycle performance diagram of the polymer electrolyte assembled lithium battery prepared in Example 1 and Comparative Example 1 at a voltage range of 2.5V to 4V and a rate of 0.5C; wherein Figure a is Example 1 and Figure b is Comparative Example 1. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] The solid electrolyte and solid battery of the fluorinated aniline derivative multifunctional additive of this embodiment are prepared by the following steps:

[0041] S1, in the argon protective atmosphere of the glove box, weigh 1 mL DOL (cyclic ether) and 0.1 g 2,4-difluoroaniline, mix them evenly, add 0.287 g LiTFSI (bis(trifluorosulfonyl)lithium sulfide, 1 mol / L) thereto, stir evenly, and stir at a speed of 600 rmin -1 , stir for 1h.

[0042] S2, add 0.1wt% of initiator aluminum trifluoromethanesulfonate to the mixed solution, and heat at 600rmin -1 The mixture was stirred at a stirring speed of 0.5 h to obtain a precursor solution after being uniformly stirred.

[0043] S3, according to the assembly method of button cells, with lithium iron phosphate (LiFePO4) as the positive electrode and lithium metal as the negative electrode, the prepared precursor solution is added to the polypropylene (PP) separator, and the button cell is assembled. The button cell is left to stand for 2 hours, and then heated at 60°C for 12 hours, the monomer is completely polymerized, and finally a polymer electrolyte lithium battery is obtained.

[0044] Example 2

[0045] The solid electrolyte and solid battery of the fluorinated aniline derivative multifunctional additive of this embodiment are prepared by the following steps:

[0046] S1, in the argon atmosphere of the glove box, weigh 1 mL of methacrylate and 0.1 g of 2,4-difluoroaniline, mix them evenly, add 0.144 g of LiDFOB (lithium difluorooxalatoborate, 1 mol / L), stir evenly, and stir at a speed of 600 rmin -1 , stir for 1h.

[0047] S2, add 0.1wt% of initiator azobisisobutyronitrile to the mixed solution, and heat at 600rmin -1 The mixture was stirred at a stirring speed of 0.5 h to obtain a precursor solution after being uniformly stirred.

[0048] S3, according to the assembly method of button cells, with lithium iron phosphate (LiFePO4) as the positive electrode and lithium metal as the negative electrode, the prepared precursor solution is added to the polypropylene (PP) separator, and the button cell is assembled. The button cell is left to stand for 2 hours, and then heated at 60°C for 12 hours, the monomer is completely polymerized, and finally a polymer electrolyte lithium battery is obtained.

[0049] Example 3

[0050] The solid electrolyte and solid battery of the fluorinated aniline derivative multifunctional additive of this embodiment are prepared by the following steps:

[0051] S1, in the argon protective atmosphere of the glove box, weigh 1g PEO (polyether) and 10g acetonitrile and mix them evenly, add 0.1g 2,4-difluoroaniline and 0.374g LiFSI (lithium bis(fluorosulfonyl)imide, 2mol / L) thereto, stir evenly, and stir at a speed of 600rmin -1 , and stirred for 1 h to obtain a precursor solution.

[0052] S2, pouring the precursor solution into a polytetrafluoroethylene mold and drying it at 60° C. for 24 hours to obtain a solid electrolyte containing a fluorinated aniline derivative multifunctional additive.

[0053] S3, according to the assembly method of button cells, with lithium iron phosphate (LiFePO4) as the positive electrode and lithium metal as the negative electrode, the prepared precursor solution is added to the polypropylene (PP) separator, and the button cell is assembled. The button cell is left to stand for 2 hours, and then heated at 60°C for 12 hours, the monomer is completely polymerized, and finally a polymer electrolyte lithium battery is obtained.

[0054] Example 4

[0055] The solid electrolyte and solid battery of the fluorinated aniline derivative multifunctional additive of this embodiment are prepared by the following steps:

[0056] S1, in the argon protective atmosphere of the glove box, weigh 1g PVDF (polyvinylidene fluoride) and 10g DMF (dimethylformamide) and mix them evenly, add 0.08g 2,4-difluoroaniline and 0.456g LiFSI (lithium hexafluorophosphate, 3mol / L) thereto, stir evenly, and stir at a speed of 600rmin -1 , and stirred for 1 h to obtain a precursor solution.

[0057] S2, pouring the precursor solution into a polytetrafluoroethylene mold and drying it at 60° C. for 24 hours to obtain a solid electrolyte containing a fluorinated aniline derivative multifunctional additive.

[0058] S3, according to the assembly method of button cells, with lithium iron phosphate (LiFePO4) as the positive electrode and lithium metal as the negative electrode, the prepared precursor solution is added to the polypropylene (PP) separator, and the button cell is assembled. The button cell is left to stand for 2 hours, and then heated at 60°C for 12 hours, the monomer is completely polymerized, and finally a polymer electrolyte lithium battery is obtained.

[0059] Example 5

[0060] The solid electrolyte and solid battery of the fluorinated aniline derivative multifunctional additive of this embodiment are prepared by the following steps:

[0061] S1, in the argon protective atmosphere of the glove box, weigh 1 mL of polyethylene glycol monomethyl ether acrylate (acrylate homologue), 0.05 g of 2,4-difluoroaniline, mix them evenly, add 0.861 g of LiTFSI (bis(trifluorosulfonyl)lithium sulfonate, 3 mol / L) thereto, and stir at a speed of 600 rmin -1 , stir for 1h, stir evenly.

[0062] S2, add 0.2wt% of initiator stannous trifluoromethanesulfonate to the mixed solution, and heat at 600rmin -1 The mixture was stirred at a stirring speed of 0.5 h to obtain a precursor solution after being uniformly stirred.

[0063] S3, according to the assembly method of button cells, with lithium iron phosphate (LiFePO4) as the positive electrode and lithium metal as the negative electrode, the prepared precursor solution is added to the polypropylene (PP) separator, and the button cell is assembled. The button cell is left to stand for 2 hours, and then heated at 60°C for 12 hours, the monomer is completely polymerized, and finally a polymer electrolyte lithium battery is obtained.

[0064] Example 6

[0065] The difference between this embodiment and embodiment 1 is that the additive is 2,4-dichloro-5-fluoroaniline, and the rest of the contents are the same as embodiment 1.

[0066] Example 7

[0067] The difference between this embodiment and embodiment 1 is that the additive is p-fluorobenzylamine, and the rest of the contents are the same as those of embodiment 1.

[0068] Example 8

[0069] The difference between this embodiment and embodiment 1 is that the additive is 2,3,4,5,6-pentafluoroaniline, and the rest of the contents are the same as embodiment 1.

[0070] Example 9

[0071] The difference between this embodiment and embodiment 1 is that the additive is 2-(4-fluorophenyl)-2-propylamine, and the rest of the contents are the same as embodiment 1.

[0072] Example 10

[0073] The difference between this embodiment and embodiment 1 is that the additive is 4-ethoxy-2-fluoroaniline, and the rest of the contents are the same as embodiment 1.

[0074] Embodiment 11

[0075] The difference between this embodiment and embodiment 1 is that the additive is 5-benzyloxy-2-fluoroaniline, and the rest of the contents are the same.

[0076] Example 12

[0077] The difference between this embodiment and embodiment 1 is that the additive is 2-amino-6-fluorobenzonitrile, and the rest of the contents are the same.

[0078] Comparative Example 1

[0079] Compared with Example 1, Comparative Example 1 lacks additives, and the specific scheme is as follows:

[0080] The solid electrolyte and solid battery of the fluorinated aniline derivative multifunctional additive of this comparative example are prepared by the following steps:

[0081] S1, in the argon protective atmosphere of the glove box, weigh 1 mL of DOL (cyclic ether), add 0.287 g of LiTFSI (1 mol / L of lithium bis(trifluorosulfonyl)imide) to it, stir evenly at a stirring speed of 600 rmin -1 , stir for 1h.

[0082] S2, add 0.1wt% of initiator aluminum trifluoromethanesulfonate to the mixed solution, and heat at 600rmin -1 The mixture was stirred at a stirring speed of 0.5 h to obtain a precursor solution after being uniformly stirred.

[0083] S3, according to the assembly method of button cells, with lithium iron phosphate (LiFePO4) as the positive electrode and lithium metal as the negative electrode, the prepared precursor solution is added to the polypropylene (PP) separator, and the button cell is assembled. The button cell is left to stand for 2 hours, and then heated at 60°C for 12 hours, the monomer is completely polymerized, and finally a polymer electrolyte lithium battery is obtained.

[0084] Comparative Example 2

[0085] Compared with Example 1, the amount of additives used in Comparative Example 2 exceeds the specified range of this application. The specific scheme is as follows:

[0086] The solid electrolyte and solid battery of the fluorinated aniline derivative multifunctional additive of this comparative example are prepared by the following steps:

[0087] S1, in the argon protective atmosphere of the glove box, weigh 1 mL DO (cyclic ether) L and 0.5 g 2,4-difluoroaniline, mix them evenly, add 0.287 g LiTFSI (lithium bis(trifluorosulfonyl)imide, 1 mol / L), stir evenly, and stir at a speed of 600 rmin -1 , stir for 1h.

[0088] S2, add 0.1wt% of initiator aluminum trifluoromethanesulfonate to the mixed solution, and heat at 600rmin -1 The mixture was stirred at a stirring speed of 0.5 h to obtain a precursor solution after being uniformly stirred.

[0089] S3, according to the assembly method of button cells, with lithium iron phosphate (LiFePO4) as the positive electrode and lithium metal as the negative electrode, the prepared precursor solution is added to the polypropylene (PP) separator, and the button cell is assembled. The button cell is left to stand for 2 hours, and then heated at 60°C for 12 hours, the monomer is completely polymerized, and finally a polymer electrolyte lithium battery is obtained.

[0090] The performance tests of the polymer electrolytes containing aniline derivatives prepared in the examples and comparative examples were carried out, namely, ionic conductivity test (test frequency was 10 6 -1Hz, amplitude 5mV), oxidation resistance test (electrochemical window), lithium stability test, the results are shown in Table 1 and Figure 1-5 shown.

[0091] Lithium stability test method: Li / / Li symmetric battery prepared with polymer electrolyte at 0.5 mA cm -2 , 0.5mAh cm -2 The voltage-time curve of the test is shown below.

[0092] Table 1 Comparison of polymer electrolyte performance

[0093]

[0094] The results in Table 1 show that the addition amount of the additive is between 1-10wt%, which is beneficial to the performance improvement of the polymer electrolyte. Beyond this range, the effect is not obvious. For example, in Example 1, under the same test conditions as Example 1, the ionic conductivity of the polymer electrolyte with an additive addition amount of 0 is significantly reduced, the electrochemical window is significantly reduced, and the polarization voltage is significantly increased; in Example 2, under the same test conditions as Example 1, the electrochemical performance of the polymer electrolyte with an additive addition amount of 50wt% is also significantly reduced. When the addition content is too low, the dissociation effect on the lithium salt is not obvious, and it is difficult to improve the solvation structure of lithium ions; and excessive additives will destroy the network structure of the polymer and reduce the transmission of lithium ions.

[0095] It can be seen from Examples 1-5 that, on the basis of the same additives, the polymer electrolyte performance varies greatly due to the different polymer matrix and additive content, among which Example 1 has the best effect. It can be seen from Examples 6-12 that, on the basis of fluorine atoms, the addition of chlorine atoms, alkoxy groups, phenyl groups or nitrile groups further improves the ionic conductivity, cycle life and antioxidant properties of the solid electrolyte. Among them, Example 12 has the best effect, indicating that the introduction of nitrile groups helps the dissociation of lithium salts, promotes the migration of lithium ions, and prolongs the cycle life of the battery.

[0096] The electrochemical impedance spectroscopy test was performed on the polymer electrolytes prepared in Example 1 and Comparative Example 1. The results are as follows: Figure 1 As shown, the impedance of the polymer electrolyte prepared in Example 1 is 2.4 ohms, and its ionic conductivity is calculated to be 8.56×10 -4 Scm -1 The fluorine atoms in the additive can improve the solvation structure of lithium ions, and their weak solvation ability can enhance the interaction between lithium ions and anions. The amino group can interact with lithium salts, promote the dissociation of lithium salts, and improve ionic conductivity. The impedance of the polymer electrolyte prepared in Comparative Example 1 is 14 ohms. By calculation, its ionic conductivity is 1.72×10 -4 Scm -1 , its ionic conductivity is relatively low and its ability to transport lithium ions is weak.

[0097] The polymer electrolytes prepared in Example 1 and Comparative Example 1 were subjected to linear sweep voltammetry tests. The results are as follows: Figure 2 As shown, the electrochemical window of the polymer electrolyte prepared in Example 1 is 5.2 V, and the electrochemical window of the polymer electrolyte prepared in Comparative Example 1 is 4.5 V. This indicates that the addition of additives can significantly improve the electrochemical window of the electrolyte, increase the oxidation potential of the electrolyte, and improve its antioxidant capacity.

[0098] The compatibility between the polymer electrolyte prepared in Example 1 and Comparative Example 1 and the lithium negative electrode was tested, and the results were as follows: Figure 3 As shown, the polymer electrolyte of Example 1 can be stably cycled for more than 300 hours, and the overpotential is about 60mV. It can be seen that the polymer electrolyte has good compatibility with the lithium negative electrode. However, the polymer electrolyte of Comparative Example 1 has a large polarization voltage. After 200 hours of circulation, the polarization voltage increases significantly, and the compatibility with lithium is poor.

[0099] The lithium sheets of the Li / / Li symmetric battery assembled with the polymer electrolyte prepared in Example 1 and Comparative Example 1 after 20 cycles were tested by scanning electron microscope. Figure 4As shown, Figure a is the surface morphology of lithium metal after the cycle of Example 1. It can be seen that the lithium deposition is relatively dense and the surface is relatively flat. However, the lithium metal morphology after the cycle of Comparative Example 1 (Figure b) is relatively loose, mossy, and the surface is uneven. It can be seen that the addition of additives can significantly improve the compatibility of polymer electrolytes and lithium metal, promote the uniform deposition of lithium, and inhibit the growth of lithium dendrites.

[0100] The cycle performance of the composite solid polymer electrolyte prepared in Example 1 and Comparative Example 1 was tested by the following method: the prepared button battery was tested for cycle performance at a voltage range of 2.5 V to 4 V at a rate of 0.5 C (1 C = 170 mAh g-1). The results are shown in FIG. Figure 5 As shown in the figure, the initial discharge capacity of the polymer electrolyte prepared in Example 1 is 153.5 mAh g -1 After 30 cycles, the battery capacity retention rate was 95.3%, and the cycle performance was relatively stable. The polymer electrolyte prepared in Comparative Example 1 had an initial discharge capacity of 142.6 mAh g -1 After 30 cycles, the battery capacity retention rate was 78.9%, and the cycle performance was poor. This shows that the addition of additives can significantly improve the stability of battery cycle performance.

[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A multifunctional additive, characterized in that: The additives include fluoroaniline and its derivatives, and the general structural formula thereof is: Wherein, R1 includes a fluorine atom; R2 is a single bond or an alkyl group, and x is an integer of 1 to 5.

2. A multifunctional additive as claimed in claim 1, characterized in that: The R1 further includes one or more of a chlorine atom, an alkoxy group, a phenyl group and a nitrile group.

3. A solid electrolyte, characterized in that: The invention comprises a lithium salt, a polymer matrix and the additive according to any one of claims 1 to 2.

4. A solid electrolyte according to claim 3, characterized in that: The dosage of the additive is 0.5%-10% of the total mass of the lithium salt and the polymer matrix.

5. A solid electrolyte according to claim 3, characterized in that: The polymer matrix is ​​one or more combinations of polyether, polyvinylidene fluoride and its homologues or cyclic ether, acrylate and its homologues; the lithium salt is one or more combinations of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluorosulfonyl)imide.

6. The method for preparing a solid electrolyte according to claim 5, characterized in that: The steps include: S1, in an argon protective atmosphere of a glove box, uniformly mixing the additive and the polymer matrix to obtain a mixed solution I; S2, mixing the mixed solution I with a lithium salt to obtain a precursor solution, and heating the solution until the solvent evaporates to obtain a solid electrolyte.

7. The method for preparing a solid electrolyte according to claim 6, characterized in that: In step S1, when the polymer matrix is ​​polyether, polyvinylidene fluoride and its homologues, it is first dissolved in an organic solvent and then mixed with the additive; The mass ratio of polymer matrix to organic solvent is (5-20):100, and the organic solvent is dimethylformamide or acetonitrile.

8. The method for preparing a solid electrolyte according to claim 6, characterized in that: In step S2, the concentration of the lithium salt is 1-3 mol / L.

9. The method for preparing a solid electrolyte according to claim 6, characterized in that: When the polymer matrix is ​​cyclic ether, acrylate and its homologues, in step S2, after the mixed solution I is mixed with the lithium salt, an initiator is added to obtain a precursor solution; the initiator is one or more combinations of aluminum trifluoromethanesulfonate, stannous trifluoromethanesulfonate and azobisisobutyronitrile, and the amount of the initiator is 0.1%-0.5% of the total mass of the mixed solution I and the lithium salt.

10. Use of the solid electrolyte according to any one of claims 3 to 5 in the preparation of lithium batteries.

Citation Information

Patent Citations

  • Additive for battery, secondary battery, battery module, battery pack and device

    CN112563571A

  • Organic-inorganic composite polymer solid electrolyte as well as preparation method and application thereof

    CN117352833A

  • Method for preparing carbon fluoride material by using fluorine-containing polymer

    CN118183708A

  • Lithium-ion secondary battery

    US20150171468A1

  • Polymer compound, intermediate composition, negative electrode, electrical storage device, slurry for negative electrode, method for producing polymer compound, and method for producing negative electrode

    US20190040199A1